Association between intraoperative intravenous lidocaine infusion and survival in patients undergoing pancreatectomy for pancreatic cancer: a retrospective study. (August 2020) - Zhang, Hao; Yang, Li; Zhu, Xuqin; Zhu, Minmin; Sun, Zhirong; Cata, Juan P.; Chen, Wankun; Miao, Changhong
Abstract: Background: Intravenous lidocaine has been shown to reduce opioid consumption and is associated with favourable outcomes after surgery. In this study, we explored whether intraoperative lidocaine reduces intraoperative opioid use and length of stay (LOS) and improves long-term survival after pancreatic cancer surgery. Methods: This retrospective study included 2239 patients who underwent pancreatectomy from January 2014 to December 2017. The patients were divided into non-lidocaine and lidocaine (bolus injection of 1.5 mg kg −1 at the induction of anaesthesia followed by a continuous infusion of 2 mg kg −1 h −1 intraoperatively) groups. The overall use of postoperative rescue analgesia and LOS were recorded. Propensity score matching was used to minimise bias, and disease-free survival and overall survival were compared between the two groups. Results: After propensity score matching, patient characteristics were not significantly different between groups. Intraoperative sufentanil consumption and use of postoperative rescue analgesia in the lidocaine group were significantly lower than those in the non-lidocaine group. The LOS was similar between groups. There was no significant difference in disease-free survival between groups (hazard ratio [HR]=0.913; 95% confidence interval [CI], 0.821–1.612; P =0.316). The overall survival rates at 1 and 3 yr were significantly higher in the lidocaine group than in the non-lidocaine group (68.0% vs 62.6%, P <0.001; 34.1% vs 27.2%, P =0.011). The multivariable analysis indicated that intraoperative lidocaine infusion was associated with a prolonged overall survival (HR=0.616; 95% CI, 0.290–0.783; P =0.013). Conclusion: Intraoperative intravenous lidocaine infusion was associated with improved overall survival in patients undergoing pancreatectomy.